BALANCED SCORECARD DALAM AKSI PENGUKURAN KINERJA : Studi pada PDAM Tirta Tampanama Kabupaten Kolaka Utara - Amalia Vicky Ferdiansyah; Abdul Hakim; I Gede Eko Putra Sri Sentanu (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
As an organization that provides services to the community, it is often found that the performance of Regional Government-Owned Company has not been able to meet their objectives. At PDAM Tirta Tampanama, indications of the problem can be seen from the financial losses suffered in the last two years. These problems need to be explored with comprehensive performance measurement. By using the Balanced Scorecard, measurements are carried out in four perspectives, including finance, customers, internal business processes, and learning and growth. The results showed that it’s the performance in 2021 was categorized as unhealthy with a performance value of 2,250.